Upaya Meningkatkan Motivasi Speaking Skill Peserta didik dalam Materi Discussion Text Menggunakan Model Pembelajaran Game-Based Learning (Alibi Games) di Kelas XII-3 SMA Negeri 4 Semarang. - Yulianti, Sari; Ifadah, Muhimatul; Niken, Maria (Journal of Lesson Study in Teacher Education, 2025)
This study examines the implementation of Game-Based Learning to improve the speaking motivation of students in class XII-3 SMA Negeri 4 Semarang. The problem addressed was the low participation of students in English lessons, particularly in speaking skills. This Classroom Action Research was conducted in two cycles, each comprising planning, action, observation, and reflection stages. Data collection was carried out through direct classroom observation and evaluation of students’ speaking presentations. The results of the first cycle showed some improvement, with 61% of the 36 students submitting video speaking assignments. In the second cycle, the integration of Cooperative Learning strategies such as the Gallery Walk led to higher student participation, with 94% achieving the target. The findings suggest that the Game-Based Learning model significantly enhances students' motivation and engagement in speaking activities.